Tradisi malam tirakatan di Desa Kemantren Kecamatan Jabung Kabupaten Malang sebagai implementasi nilai religius - Sidiq, Muhammad Umar (Maliki Interdisciplinary Journal, 2024)
Tradition is an activity that is carried out continuously so that it becomes a habit in a society that is adjusted to religious rituals in a particular custom. This article aims to find out how the Night of Tirakatan Tradition in Kemantren Village, Jabung District, Malang Regency as an Implementation of Religious Values. This article uses a research method that uses a method The research method used in this study is to use a qualitative method, by conducting observations Regarding the Night of Tirakatan Activities carried out in Kemantren Village, Jabung District, Malang Regency. The objects targeted in this tradition are all residents of Kemantren Village. The results of the Night of Tirakatan Tradition teach the importance of solidarity, equality, and a sense of responsibility in community life. These values strengthen social relations and show how togetherness can be a tool to maintain balance in a Community.